Board influence on accruals management and the role of ownership structure: Evidence from Bangladesh - Hasan, Mohammad Tariq; Rekabder, Mohammad Sarwar; Hasan, Md Mahmood Ul Haque; Kuri, Pranto Kumar (Asian Economic and Financial Review, 2023)
The main purpose of this study is to explore the association between accruals management (AM) and board attributes. Additionally, the study investigates the moderating role of ownership structures. In order to perform the study, five years of data (2016–2020) for 159 firms listed on the Dhaka Stock Exchange (DSE) have been considered, consisting of 759 firm-year observations. Agency theory that governs the relationship between the principal and the agent has been applied here. We have used STATA software with the random effects GLS model to run the regression on the balanced panel data. The results of the analysis show that, while board size and board independence have significant positive relation with AM, gender diversity, institutional ownership and family ownership show a significant negative association with AM. The analysis of moderating variables shows that foreign ownership has a significant negative impact on the association between board expertise and AM, and family ownership has a significant negative impact on board independence and AM. These findings indicate that the type of ownership structure may be useful in attaining the objectives of the board in Bangladesh. The findings of the study will be relevant for the regulatory authorities in Bangladesh in controlling and implementing new guidelines related to corporate governance.